Electronic, Spectral and Structural Characteristics of Carbon Nanotubes: Gallium nitride as an optoelectronic Applications - Mohammed Jawad H. Kadhim; Ali S. Hasan; Q. A. AL-Jarwany (Genius Journals, 2022)
In this paper, the electronic, structural and spectral characteristics of GaN -grafted CNT prepared by chemical vapor deposition method, are studied. New models of CNT and CNT/GaN have been prepared and designed by DFT/B3LYP technique with SDD base groups. Surface morphology, electronic transitions, and structural characteristics have been determined by Gaussian 09 program package. The electronic results gave the total energy, the energy gap, the highest occupied energy level (HOMO) and the lowest free energy level (LUMO). The surface morphology of thin CNT/GaN were observed by Scanning Electron Microscope (SEM), Furthermore, it has been utilized orbital analysis, counting the states density (DOS) to find the possible orbital hybridization for molecules, thus determining the optoelectronic effectiveness of the molecules under study. Through research, we can benefit from the results within optical applications and Nano film technology, with its high electronic and spectral characteristics.
Keywords: Structural; electronic transitions properties; DFT; optoelectronic Applications